Effectiveness of Sirsak Fruit Juice Therapy to Decreasing Elderly Acid Acid Levels in Tresna Werdha Social Beach Pagar Dewa Bengkulu - Dian Dwiana; Santoso Ujang Effendi; Vusva Vaudyah (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2019)
Uric acid is the end product or a waste product resulting from the metabolism/ breakdown of purines .. The purpose of this study was to determine the effectiveness of Soursop fruit juice therapy to decrease uric acid levels in the Elderly Social Institution Tresna Werdha Pagar Dewa Bengkulu year 2018. The design of this Penenlitian pre- experimental. The population in this study who had the Uric Acid in Elderly Social Institution Tresna Pagar Dewa Bengkulu which amount 17 people. The sampling technique used Total sampling technique. Collecting data in this study is the observation uric acid levels before and after therapy soursop juice for 2 minggu..Hasil research showed: (1) there are 17 people (100%) with high levels of uric acid 6 mg / dl; (2) there are 13 people (76.5%) had decreased levels of uric acid, and 4 (23, 5%) who did not experience decreased levels of uric acid; (3) No effect Soursop fruit juice therapy to decrease uric acid levels in the Elderly Social Institution Tresna Werdha Pagar Dewa Bengkulu. Keywords: elderly, uric acid, soursop juice